(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The information offered in About Iberia (Iberiké), 51-54, constitutes an obvious case of neglect towards Appian. The inaccurate and slovenly treatment given to the passage is crowned by the confusing use of Vacceans as Celtiberians. Surely Appian shows the maximum lack of interest in ethnographic precision, using Vacceans in a rhethorical fashion: innocent as they are, caught in the middle of the war against the Celtiberians, they are the object of the republican perfidy of L. Licinius Lucullus, who is the true protagonist of this fragment.